Three-dimensionally architectured tungsten trioxide/tungsten trioxide hydrate/carbon cloth composite as a binder-free anode for lithium-ion batteries. Issue 3 (3rd May 2020) - Lin, Xi; Li, Wanjiao; Yao, Yuxiu; Lv, Chunju
Abstract: The exploration of suitable host structures as anodes is essential for lithium-ion batteries. In this work, a three-dimensionally architectured tungsten trioxide/tungsten trioxide hydrate/carbon cloth composite was synthesized by a simple and cost-effective hydrothermal process. The obtained tungsten trioxide/tungsten trioxide hydrate/carbon cloth composite was directly used as the binder-free electrode and evaluated as an anode for lithium-ion batteries by cyclic voltammetry, galvanostatic discharge-charge measurements, and electrochemical impedance spectroscopy. The binder-free electrode exhibits a high reversible lithium storage capacity of 825 mA h g −1 after 100 cycles at a current density of 0.1 A g −1 . When cycled at a current density of 2 A g −1, a capacity of 309 mA h g −1 remained. The excellent electrochemical performance may be due to the unique self-assembled tungsten trioxide/tungsten trioxide hydrate nanorods on the carbon cloth conductive substrate with a three-dimensional architecture.